If it's not what You are looking for type in the equation solver your own equation and let us solve it.
72=-9xx2
We move all terms to the left:
72-(-9xx2)=0
We get rid of parentheses
9xx2+72=0
We move all terms containing x to the left, all other terms to the right
9xx2=-72
x=-72/1
x=-72
| 14=c2+ 12 | | (2/3)w-1/2=1/4 | | y+3=2y+4 | | -2j+16.52=2.52 | | 9+b/4=7 | | -11(x+26)-27(x+26)=15x-15 | | 3x+-8=15 | | 6=j2− –4 | | 2x-8x-13=6x+5-13 | | 7.5x+30=x | | j/4+27=35 | | -5+2x/5=5 | | 8x+4x=-15-9 | | 5.6➗0.4-r=-8 | | -6+2x/5=0 | | -2d+-8.09=-1.85 | | 2(x-1)/3=2(x+5)/9 | | 2m-31=23 | | 2/3(3x-9)=-2(2x+6) | | 7h-10=67 | | 72=−9x2 | | 10=-8-50+3y | | 6f+9=51 | | 86=-7a+2 | | 3.2/12.6=g | | 86=−7a+2 | | 48=6(f+2) | | -4.3-14.5=n | | 6(x-1)/40=3(x+2)/40 | | 90=13+11y | | 12z+23=-109 | | 135=15x-15 |